Segregations språk: Riksdagens öppna data: Kammaraktiviteter - Språkbanken Text (University of Gothenburg, 2025)
Texts that treat segregation
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik